PANDEMI COVID-19: PERAN GENERASI MILENIAL DALAM MENGHADAPI DAMPAK TANTANGAN BISNIS DI INDONESIA - Arda Jiter Nurda; Muhammad Iqbal Fasa; Soeharto Soeharto (LP2M Universitas Bina Bangsa, 2022)
Economically, socially and politically not only big countries but almost all countries in the world. Indonesia is one of the affected countries, especially from an economic perspective. Indonesia, which is dominated by Micro, Small and Medium Enterprises (MSMEs), needs special attention to these sectors because the contribution of MSMEs to the national economy is quite large. This journal aims to analyze the impact of the COVID-19 pandemic on the existence of MSMEs in Indonesia and how solutions can help MSMEs survive in the COVID-19 pandemic situation